Matematika di balik fenomena alam: Dari Fibonacci hingga Fraktal - Nuryanawati, Ita (Maliki Interdisciplinary Journal, 2024)
Mathematics plays a vital role in understanding the universe. This article aims to uncover how mathematical concepts such as the Fibonacci sequence and Fractals are closely related to the fabric of life and the environment. The Fibonacci sequence, discovered by Leonardo Fibonacci in the 13th century, is present in many forms in nature, such as sunflower patterns, snail shell spirals, and crystal structures. On the other hand, the concept of Fractals, introduced by Benoit Mandelbrot in 1975, helps explain complex structures that repeat themselves at various scales, such as snowflakes, tree bark, mountain shapes, and coastlines. The mathematical properties of the Fibonacci sequence and Fractals provide deep insights into how these patterns form and evolve in nature, demonstrating the close connection between mathematics and nature.